2020
DOI: 10.1002/berj.3684
|View full text |Cite
|
Sign up to set email alerts
|

Should value‐added school effects models include student‐ and school‐level covariates? Evidence from Australian population assessment data

Abstract: There is an enduring issue on whether student-and school-level covariates should be included in value-added school effects models, in addition to prior achievement. Proponents argue that the addition of covariates allows fairer comparisons of schools, whereas opponents argue that it excuses poorly performing schools and obscures policy-relevant school differences. School-level covariates are problematic statistically, but it has been argued that mean school prior achievement should be included in school effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…For Australia, intradomain correlations in the National Assessments-Literacy and Numeracy (NAPLAN) range from 0.6 to 0.9 and are higher for numeracy and spelling than for other domains, and higher in secondary school than in primary school (Marks, 2021). For Germany, the correlation in mathematics test scores (one based on PISA) taken one year apart in 2003 and 2004 was 0.73 (Kriegbaum et al, 2015).…”
Section: High Intradomain Correlationsmentioning
confidence: 99%
“…For Australia, intradomain correlations in the National Assessments-Literacy and Numeracy (NAPLAN) range from 0.6 to 0.9 and are higher for numeracy and spelling than for other domains, and higher in secondary school than in primary school (Marks, 2021). For Germany, the correlation in mathematics test scores (one based on PISA) taken one year apart in 2003 and 2004 was 0.73 (Kriegbaum et al, 2015).…”
Section: High Intradomain Correlationsmentioning
confidence: 99%
“…For example, if the association between poverty and lower performance chiefly reflects the impact of poorer teaching standards in deprived areas (rather than being driven by factors external to the school environment) then controlling for student disadvantage might remove this variation despite it being an important component to how well a school is serving its student population (Perry, 2016). Marks (2020) also argues that adjusting for student background characteristics may well introduce measurement issues.…”
Section: Adjustments For Pupil Prior Attainment and Pupil Backgroundmentioning
confidence: 99%
“…In Pakistan, generally, while in Sindh mainly, English language teaching, learning, and assessment have remained a significant challenge for students and teachers. According to the views shared in [3], to use assessment more, assessment should also be an element that can motivate students to learn [4]. It has been shown that assessment tools should be used to assess or evaluate students' achievement and enhance the quality of language learning and teaching, but this is missing in the Pakistani context and is one of the main issues of assessment.…”
Section: Introductionmentioning
confidence: 99%